Realized the importance of practice and smart approach to a problem.

Dark Mode

2,564 views

26 votes

Best answer

Answer: D

Since $r$ is a root of the given equation $\text{}x^2+2x+6=0, \\ $ So, $r$ will satisfy this equation. Hence, we have $r^2+2r+6=0$

$\Rightarrow \boxed{r^{2} + 2r = -6}$

The value of expression $ (r+2)(r+3)(r+4)(r+5)\\ = (r^2+5r+6)(r^2+9r+20)\\ = (r^2+2r+6+3r)(r^2+2r+6+14+7r)\\

=(3r)(7r+14)\\=

21(r^2+2r)\\ =

21 \times -6 \\ =

\color{blue}{-126}.$

Since $r$ is a root of the given equation $\text{}x^2+2x+6=0, \\ $ So, $r$ will satisfy this equation. Hence, we have $r^2+2r+6=0$

$\Rightarrow \boxed{r^{2} + 2r = -6}$

The value of expression $ (r+2)(r+3)(r+4)(r+5)\\ = (r^2+5r+6)(r^2+9r+20)\\ = (r^2+2r+6+3r)(r^2+2r+6+14+7r)\\

=(3r)(7r+14)\\=

21(r^2+2r)\\ =

21 \times -6 \\ =

\color{blue}{-126}.$